UMPSA collaboration with BAEG and PKPB in international mobility strengthens Advanced TVET - Mimi Rabita, Abd Wahit (UMPSA, 2024)
BEIJING, 29 May 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) collaborated with BEIFANG Automotive Education Group (BAEG) and the National Organisation of Skilled Workers (BELIA MAHIR) in Technical and Vocational Education and Training (TVET) to undergo upskilling training in producing industry-available skilled professional workforce for career development and graduate employability (GE) in Malaysia.